Investigation of parameters of the working substance - low temperature plasma in the ionization resonator chamber of the RF reactive engine - Vdovin, V.S.; Zajtzev, B.V.; Kobetz, A.F.; Rudiak, B.I.; Bomko, V.A.; Lesnykh, M.S.; Zhuravlev, V.G.; Rashkovan, V.M.; Bazyma, L.A.; Basteev, V.A.; Belokon, V.I. (Вопросы атомной науки и техники, 2003)
This paper is the extension of investigations of the RF engine designed for orientation and stabilization of the spacecrafts orbit, and it is undertaken for measuring of plasma parameters of RF discharge in the ionization resonator chamber. The experiments were performed at the frequency of 80 MHz on the model engine, in which a length of coaxial line with shortening capacities at the ends was used as the ionization resonator chamber. As the result of the experiments, conditions of the RF discharge ignition in the resonator chamber are studied; dependencies of plasma density and temperature versus applied power and working body pressure are obtained for various gases. The measurements of the thrust were performed at the special-purpose test bench. The data obtained allow making a conclusion that further investigations in this direction hold much promise. Представлена робота продовжує дослідження НВЧ – двигуна, призначеного для орієнтації та стабілізації орбіти космічних апаратів, й виконана з метою виміряти параметри плазми НВЧ – розряду в іонізаційній камері – резонаторі двигуна. Експерименти проводились з частотою 80 МГц на макеті двигуна, в якому в якості іонізаційної камери використовувався відрізок коаксиальної лінії зі скорочуваючими ємностями на кінцях. В експериментах вивчені умови запалювання НВЧ – розряду в камері–резонаторі, отримані залежності густини та температури плазми від прикладеної потужності та тиску робочого тіла для різних газів. На спеціалізованому випробному стенді були проведені вимірювання тяги. Отримані результати дозволяють зробити висновок про перспективність подальших досліджень у цьому напрямку. Настоящая работа является продолжением исследований СВЧ – двигателя предназначенного для ориентации и стабилизации орбиты космических аппаратов и предпринята с целью измерения параметров плазмы СВЧ – разряда в ионизационной камере – резонаторе двигателя. Эксперименты проводились на частоте 80 МГц на макете двигателя, в котором в качестве ионизационной камеры – резонатора использовался отрезок коаксиальной линии с укорачивающими емкостями на концах. В экспериментах изучены условия зажигания СВЧ разряда в камере - резонаторе, получены зависимости плотности и температуры плазмы от приложенной мощности и давления рабочего тела для различных газов. На специализированном испытательном стенде были проведены измерения тяги. Полученные данные позволяют сделать вывод о перспективности дальнейших исследований в этом направлении.